Certain Idioms and Their Meaning in the English Language - Kokanova Nursuliu Jenisbay qizi; Askarova Nafisa Avazovna (Genius Journals, 2023)
At a time when the volume and quality of data are increasing as a result of the development of modern technologies, it is also important to choose from the given data the ones that are necessary and easy to use. The field of English is very rich and it can be difficult to organize and receive the information in it in a short time. Idiom (Greek: ídios - "characteristic", "uniqueness") - a type of phraseology; a unit of speech or phrase that is unique to a particular languageand cannot be exactly translated into other languages.
Keywords: idioms; meaning of the word; phrase; phraseology